Efektivitas Kebijakan Fiskal melalui Bantuan Program Keluarga Harapan Perspektif Maqashid Syariah - Malik, Anas; Wakhid, Ali Abdul; Imtihanah, Ani Nurul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Fiscal policy is one of the main instruments used by the government to overcome poverty and improve social welfare. Through the management of state revenue and expenditure, the government can encourage economic growth, create jobs, and provide social services for the underprivileged through the Family Hope Program. This article aims to analyze the effectiveness of the Family Hope Program in poverty alleviation efforts, identify fiscal policy challenges in the implementation of the program, and review the effectiveness of PKH fiscal policy from the perspective of maqashid sharia. This study uses a qualitative method with a descriptive-analytical approach, through literature studies and secondary data analysis obtained from official government documents, research reports, and relevant scientific publications. The types of analysis used are content analysis to examine fiscal policy in the implementation of PKH, and normative analysis to assess its compliance with the principles of maqashid sharia. The results of the study indicate that the Family Hope Program is effective in increasing household income, reducing absolute poverty rates, expanding access to education and health services, and improving the socio-economic status of beneficiary families. From the perspective of maqashid sharia, PKH contributes to the protection of five main aspects, namely religion, soul, mind, descendants, and property, which as a whole reflect support for achieving community welfare.